Results of surgical treatment of infrarenal abdominal aortic aneurysms (2015)
Introduction: Surgical treatment outcomes for infrarenal abdominal aortic aneurysm repair depend on patient factors and attending vascular team expertise. Objetives: To describe the outcomes of surgical treatment of abdominal aortic aneurysm performed by an interdisciplinary team and to evaluate the effects of annual caseload and acquired expertise. Methods: Historic cohort of patients with abdominal aortic aneurysm diagnosis surgically trea-ted from January 1994 to June 2013. Three groups were established: Group 1 was for openruptured abdominal aortic aneurysm repair, Group 2 was for open elective repair and Group 3 was for elective endovascular aneurysm repairs. Primary outcome was in-hospital mortality, andsecondary outcomes were peri-procedural morbidity. For analysis the cohort was divided in two: cases repaired from 1994 to 2002 and from 2002 to 2013. This was based in the implementation of endovascular therapy from 2002 at the institution.Results: 573 patients were treated; Group 1: 65 patients; Group 2: 433 patients; Group 3: 75 patients. Mortality was 28.6%, 2.8% and 1.3% respectively. A significant rise in annual case-load (233%) was demonstrated and a trend toward lowering in surgical mortality (4.8 vs. 2.0%,p = 0.19) after 2002. Conclusions: Implementation of endovascular repair has contributed to rising annual caseloadof patients with abdominal aortic aneurysm at our institution. This rising in volume correlateswith effective lowering in mortality. © 2015 Sociedad Colombiana de Cardiología y Cirugía Cardiovascular.